Green and efficient reinforced artificial board and preparation method thereof
Through the synergistic effect of fluorosilane, aqueous acrylic emulsion, bio-based resin and nanocellulose, high-strength, moisture-proof and environmentally friendly reinforced artificial boards are prepared, solving the problems of easy expansion and release of harmful substances in humid environments, and achieving a combination of high performance and environmental protection.
Patent Information
- Application Number
- CN202510599286.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-10
- Publication Date
- 2025-07-29
AI Technical Summary
Traditional artificial boards are prone to expanding, attenuating strength in humid environments, release harmful substances, and have complex production processes, making it difficult to achieve collaborative design of high performance and environmental protection.
The solution method is used to mix the fluorosilane hydrophobic material with aqueous acrylic emulsion and bio-based resin, and nanocellulose is added. The enhanced hydrophobic mixture is prepared by ultrasonic dispersion technology, and it is uniformly dispersed with the raw materials of the artificial board and then heat-pressed.
Significantly improve the bending strength and moisture resistance of artificial boards, reduce water absorption and formaldehyde emission, simplify production processes, and is suitable for high humidity and temperature change environments.
Smart Images

Figure CN120382539A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wood-based panels, and particularly relates to a green and highly efficient reinforced wood-based panel and a preparation method thereof. Background Art
[0002] As a core material in the fields of construction and home furnishing, the performance of wood-based panels directly affects structural safety and service life. Traditional wood-based panels mostly use wood chips or fibers as the base material and are adhesively formed through synthetic resins. However, such materials are prone to problems such as moisture absorption and swelling, and strength attenuation when exposed to a humid environment for a long time, severely restricting their application in high-end scenarios. In addition, in order to improve moisture resistance and mechanical properties, formaldehyde-based resins or fluorine-containing water repellents are often added during production, resulting in the release of volatile harmful substances, threatening human health and environmental safety.
[0003] In recent years, in response to the above problems, the industry has tried to optimize through material modification. For example, nano-cellulose is used as a reinforcing phase, and its high specific surface area and mechanical properties are used to improve the matrix strength. However, it is difficult to form a stable hydrophobic network by simply adding nano-cellulose, and the moisture-proof effect is limited; although introducing fluorosilane-based water repellents can reduce the water absorption rate, due to poor interfacial compatibility with cellulose, it is easy to cause stress concentration, which instead weakens the overall strength. On the other hand, some studies have turned to bio-based resins (such as starch, soy protein) to replace traditional adhesives, but their bonding strength and water resistance are insufficient and difficult to meet high-strength requirements. It can be seen that existing technologies mostly focus on improving single performance, lacking the collaborative design of mechanical enhancement, moisture-proof durability, and environmental protection, and complex processes further push up production costs.
[0004] Therefore, there is an urgent need to develop a wood-based panel preparation scheme that takes into account high performance and green environmental protection. Through material innovation and process optimization, break through the bottleneck of the difficult balance between strength, moisture-proof, and environmental protection in traditional technologies, and provide new ideas for the sustainable development of the wood-based panel industry. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide a green and highly efficient reinforced wood-based panel and a preparation method thereof to solve the problems of insufficient mechanical properties, easy moisture absorption and swelling, formaldehyde release, and complex process of traditional wood-based panels.
[0006] To achieve the above purpose, the present invention provides the following technical solutions:
[0007] A preparation method of a green and highly efficient reinforced wood-based panel, comprising the following steps:
[0008] S1. Dissolve the fluorosilane hydrophobic material in the aqueous acrylic emulsion by the solution method, and at the same time add an appropriate amount of bio-based resin, and use ultrasonic dispersion technology to treat to obtain a uniform reinforced hydrophobic mixture;
[0009] S2. Add nanocellulose to the enhanced hydrophobic mixture in step S1 and conduct sufficient mixing treatment to construct an enhanced matrix and improve the preliminary uniformity of the material.
[0010] S3. Gradually add the enhanced hydrophobic mixture obtained in step S2 to the processed raw wood-based panel materials while conducting uniform dispersion to ensure the sufficient distribution of the enhancer and the hydrophobic material.
[0011] S4. Apply sizing treatment to the raw materials mixed in step S3, and then form them through a hot pressing process to obtain a green and highly efficient enhanced wood-based panel.
[0012] As an optional solution, the fluorosilane in step S1 is one or more of 3,3,3-trifluoropropyltriethoxysilane and hexadecafluorohexyltriethoxysilane.
[0013] As an optional solution, the bio-based resin in step S1 is one or more of soy protein resin, starch-based resin, or polylactic acid resin.
[0014] As an optional solution, the nanocellulose in step S2 is cellulose nanocrystals or cellulose nanofibers prepared by mechanical treatment or enzymatic hydrolysis methods.
[0015] As an optional solution, the mass ratio of the fluorosilane, aqueous acrylic emulsion, and bio-based resin in step S1 is (1 - 5):(10 - 30):(5 - 20).
[0016] As an optional solution, the treatment time of ultrasonic dispersion in step S1 is 10 - 20 minutes, and the frequency is 20 - 30 kHz.
[0017] As an optional solution, the weight ratio of the enhanced hydrophobic mixture to the raw wood-based panel materials in step S3 is (5 - 20):100.
[0018] As an optional solution, the hot pressing temperature of the sized raw materials in step S4 is 160 - 190 °C, the pressure is 4 - 7 MPa, and the time is 5 - 12 minutes.
[0019] As an optional solution, the moisture content of the prepared green and highly efficient enhanced wood-based panel is controlled below 8%.
[0020] Meanwhile, the present invention also provides a green and highly efficient enhanced wood-based panel prepared by the above-mentioned preparation method of the green and highly efficient enhanced wood-based panel.
[0021] Due to adopting the above technical solution, the present invention will have the following beneficial effects:
[0022] First, by constructing a three-dimensional reinforcement network with nanocellulose and optimizing the interface between fluorosilane hydrophobic material and bio-based resin, the flexural strength and structural stability of the wood-based panel are significantly improved, overcoming the problems of limited mechanical gain of a single reinforcement phase or weak interfacial bonding. Second, fluorosilane and waterborne acrylic emulsion form a dense hydrophobic layer, which, combined with the physical barrier effect of nanocellulose, endows the wood-based panel with long-term moisture-proof ability without the need for harmful additives, avoiding moisture absorption swelling and strength attenuation. Third, the use of formaldehyde-free waterborne acrylic emulsion and renewable bio-based resin eliminates the release of toxic substances; ultrasonic dispersion technology ensures the uniform distribution of the reinforcing agent, simplifies the complex process of multi-step modification in the traditional process, and reduces production costs. Compared with the existing technology, the present invention takes into account weather resistance and environmental adaptability while improving mechanical strength, is applicable to harsh environments such as high humidity and variable temperature differences, and breaks through the limitation of single performance of traditional wood-based panels. Description of the Drawings
[0023] Figure 1 It is a TEM image of the mixture of the nanocellulose solution, fluorosilane, waterborne acrylic emulsion and bio-based resin of the present invention;
[0024] Figure 2 It is a stress-strain curve graph of the green and highly efficient reinforced wood-based panel described in Example 1;
[0025] Figure 3 It is a broken line graph of the water absorption rate of the green and highly efficient reinforced wood-based panel described in Example 1. Detailed Embodiments
[0026] The technical solutions of the present invention will be further specifically described below through specific examples. In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods and equipment in the following examples are conventional methods and equipment in the art unless otherwise specified.
[0027] Example 1
[0028] This example provides a preparation method of a green and highly efficient reinforced wood-based panel, including the following steps:
[0029] 1. Pretreatment of raw materials:
[0030] Soak biomass fibers (bamboo fibers) in 5% ammonia water solution for 12 hours, perform delignification treatment with 2M sodium hydroxide and 1M sodium sulfite (treatment temperature 80 °C, time 2 hours), wash to neutral, and bleach with 3% hydrogen peroxide for 30 minutes to obtain purified cellulose raw materials.
[0031] 2. Preparation of nanocellulose:
[0032] Disperse 2 g of purified cellulose in 100 ml of deionized water, and treat it with an ultrasonic crusher (frequency 25 kHz, temperature 30 °C) for 15 minutes to obtain a uniform cellulose nanofiber suspension.
[0033] 3. Preparation of enhanced hydrophobic mixture:
[0034] According to the mass ratio of fluorosilane: waterborne acrylic emulsion: bio-based resin = 3:20:10, add 3 g of hexadecafluorohexyltriethoxysilane, 20 g of formaldehyde-free waterborne acrylic emulsion, and 10 g of soy protein resin to the cellulose suspension, and treat it with an ultrasonic oscillator (frequency 30 kHz, temperature 35 °C) for 15 minutes to obtain a uniform enhanced hydrophobic mixture. As can be seen from the TEM image ( Figure 1 ), the enhancer is uniformly distributed and firmly bonded to the cellulose surface.
[0035] 4. Mixing and sizing:
[0036] Add the enhanced hydrophobic mixture to 1300 g of pretreated wood-based panel raw materials (sawdust and starch-based binder are mixed at a ratio of 7:3) according to a weight ratio of 15:100, and disperse it evenly by mechanical stirring, and then dry it at 60 °C until the moisture content ≤ 8%.
[0037] 5. Hot pressing and forming:
[0038] The sized raw materials are hot pressed in a hot press at a pressure of 5 MPa and a temperature of 180 °C for 10 minutes to obtain a green and highly efficient enhanced wood-based panel.
[0039] This example also provides a green and highly efficient enhanced wood-based panel prepared by the above preparation method. Performance tests are carried out on it, and the results are as follows:
[0040] As Figure 2 shown, the flexural strength of the green and highly efficient enhanced wood-based panel provided in this example is 48 MPa, which is much higher than the flexural strength of traditional wood-based panels: 28.5 MPa; as Figure 3 shown, the water absorption rate (24 h) of the green and highly efficient enhanced wood-based panel provided in this example is 4%; which is much lower than the water absorption rate (24 h) of traditional wood-based panels: 14.2%.
[0041] Example 2
[0042] This example provides a preparation method of a green and highly efficient enhanced wood-based panel, including the following steps:
[0043] 1. Pretreatment of raw materials:
[0044] After soaking biomass fibers (wood fibers) in ammonia water for 24 hours, they are delignified with 5M sodium hydroxide and 2.5M sodium sulfite (treatment temperature: 90°C, time: 3 hours). After washing to neutrality and bleaching, purified cellulose is obtained.
[0045] 2. Preparation of nanocellulose:
[0046] Disperse 4g of purified wood fibers in an acetic acid buffer solution with a pH of 4.8, add cellulase (enzyme activity: 15U / g), and react at 50°C for 24 hours. Centrifuge to remove undegraded components to obtain a suspension of cellulose nanocrystals.
[0047] 3. Preparation of enhanced hydrophobic mixture:
[0048] According to the mass ratio of fluorosilane: waterborne acrylic emulsion: bio-based resin = 5:30:15, add 5g of trifluoropropyltriethoxysilane, 30g of waterborne acrylic emulsion, and 15g of polylactic acid resin to the cellulose suspension, and treat it with an ultrasonic oscillator (frequency: 25kHz, temperature: 30°C) for 20 minutes to obtain a uniform enhanced hydrophobic mixture.
[0049] 4. Mixing and sizing:
[0050] Add the enhanced hydrophobic mixture to 1300g of pretreated wood-based panel raw materials (sawdust and starch-based binder are mixed at a ratio of 6:4) according to a weight ratio of 20:100, disperse them evenly by mechanical stirring, and then dry them at 50°C until the moisture content reaches 7.5%.
[0051] 5. Hot pressing and forming:
[0052] The sized raw materials are hot pressed in a hot press at a pressure of 7MPa and a temperature of 190°C for 8 minutes to obtain a green and highly efficient enhanced wood-based panel.
[0053] This example also provides a green and highly efficient enhanced wood-based panel prepared by the above preparation method. Its performance is tested, and the results are as follows:
[0054] The flexural strength is 52.5MPa, which is much higher than the flexural strength of 28.5MPa of traditional wood-based panels; water absorption rate (24h): 3.2%, which is much lower than the water absorption rate (24h) of 14.2% of traditional wood-based panels.
[0055] The following will prove the technical effects of the present invention through comparative experiments:
[0056] (1) Setting of the control group:
[0057] 1. Traditional wood-based panel: Without adding any reinforcing agents (nanocellulose, fluorosilane, bio-based resin), only using basic materials and ordinary processes.
[0058] 2. Single enhancer group: Nano-cellulose, fluorosilane or bio-based resin was added separately to verify the independent effect of each component.
[0059] 3. Partial combination group: For example, nano-cellulose + fluorosilane (without bio-based resin), or fluorosilane + bio-based resin (without nano-cellulose) to analyze the synergistic effect.
[0060] Test indicators:
[0061] Mechanical properties: Flexural strength, elastic modulus.
[0062] Moisture-proof performance: Water absorption rate (24 hours), wet expansion rate.
[0063] Environmental protection: Formaldehyde release amount, VOC content.
[0064] Durability: Performance retention rate after damp heat cycle, weather resistance test (such as ultraviolet aging).
[0065] Standardization of experimental conditions:
[0066] All experimental groups and control groups used the same raw material source and pretreatment process.
[0067] The test method shall comply with national standards (such as GB / T 17657), and the experimental parameters (such as test temperature, humidity, instrument model) shall be recorded in detail.
[0068] (2) Test results
[0069] Table 1: Comparison data of flexural strength and water absorption rate
[0070]
[0071] Table 2: Comparison data of durability and environmental protection
[0072]
[0073] (3) Data analysis and description
[0074] 1. Flexural strength
[0075] The flexural strength of traditional wood-based panels is only 28.5 MPa. Adding nano-cellulose or fluorosilane alone can increase it to 34 - 36 MPa, but the effect is limited. In Examples 1 and 2 of the present invention, through the synergistic effect of three components, the flexural strength reaches 48 MPa and 52.5 MPa respectively, which is about 33% - 55% higher than that of traditional panels.
[0076] 2. Water absorption rate and wet expansion rate
[0077] Conventional wood-based panels have a water absorption rate of up to 14.2% and a moisture expansion rate of 1.8%, making them susceptible to deformation due to moisture. Fluorosilane alone can reduce water absorption to 7.3%, but when combined with the dense network of nanocellulose (Example 1), water absorption is further reduced to 3.2%, with a moisture expansion rate of only 0.4%.
[0078] 3. Environmental performance
[0079] The formaldehyde emission of traditional artificial boards is 0.15mg / m 3 , exceeding the environmental protection standard (GB / T 17657-2013 requirement ≤0.05mg / m 3 ). Examples 1 and 2 of the present invention use formaldehyde-free water-based acrylic emulsion and bio-based resin, and the formaldehyde emission is less than 0.01 mg / m 3 , total VOC emission ≤50μg / m 3 , meeting the green building materials certification requirements.
[0080] 4. Durability
[0081] While conventional wood-based panels retained only 65% of their strength after heat and humidity cycling, Examples 1 and 2 of the present invention achieved 93% and 96%, respectively, demonstrating excellent stability in high-humidity environments. QUV aging tests revealed no surface cracking or discoloration, demonstrating significantly better weather resistance than the control panel.
[0082] (IV) Explanation of technical mechanism
[0083] Reinforcing effect of nanocellulose: Nanocellulose forms a three-dimensional network structure through hydrogen bonding and mechanical interlocking effects, effectively dispersing stress and improving bending strength and elastic modulus.
[0084] Hydrophobic effect of fluorosilane: Fluorosilane forms a low surface energy protective layer on the surface of the material, preventing moisture penetration and reducing water absorption and wet expansion.
[0085] Interface optimization of bio-based resins: Bio-based resins (such as soy protein) act as binders to improve the interfacial bonding between nanocellulose and the substrate, reduce defects, and inhibit the agglomeration of the reinforcing agent.
[0086] (V) Conclusion
[0087] The present invention successfully produces a high-efficiency reinforced artificial board with high strength, excellent moisture resistance and environmentally friendly properties through the synergistic effect of nanocellulose, fluorosilane hydrophobic materials and bio-based resins. Compared with traditional artificial boards and single-component improvement solutions, the present invention has improved bending strength (increased by 33%-55%), water absorption (reduced to 4%-3.2%), formaldehyde emission (≤0.008mg / m 3) and durability (the retention rate of humidity and heat cycle strength ≥ 95%) have achieved breakthrough improvements, and the process is simplified and the cost is controllable. The experimental data fully verifies the technical advantages of multi-component collaborative design, provides an innovative solution for the high-end and environmental protection of wood-based panels, is applicable to high-demand scenarios such as construction and home furnishing, and has significant industrial application prospects.
[0088] The above general description of the invention involved in this application and the description of its specific embodiments should not be construed as limiting the technical solution of the invention. Those skilled in the art can, based on the disclosure of this application, without departing from the constituent elements of the invention involved, add, subtract or combine the disclosed technical features in the above general description or / and embodiments to form other technical solutions that fall within the protection scope of this application.
Claims
1. A preparation method for a green and highly efficient enhanced wood-based panel, characterized in that, It includes the following steps: S1. Dissolve the fluorosilane hydrophobic material in the aqueous acrylic emulsion by the solution method, add an appropriate amount of bio-based resin at the same time, and use the ultrasonic dispersion technology to obtain a uniform enhanced hydrophobic mixture; S2. Add the nanocellulose to the enhanced hydrophobic mixture in step S1, and perform sufficient mixing treatment to construct an enhanced matrix and improve the preliminary uniformity of the material; S3. Gradually add the enhanced hydrophobic mixture obtained in step S2 to the treated raw wood-based panel materials, and perform uniform dispersion at the same time to ensure the full distribution of the enhancer and the hydrophobic material; S4. Apply sizing treatment to the raw materials mixed in step S3, and then form them through a hot pressing process to obtain a green and highly efficient enhanced wood-based panel.
2. The preparation method of the green and highly efficient enhanced wood-based panel according to claim 1, wherein, The fluorosilane in step S1 is one or more of 3,3,3-trifluoropropyltriethoxysilane and hexadecafluorhexyltriethoxysilane.
3. The preparation method of the green and highly efficient enhanced wood-based panel according to claim 1, characterized in that, The bio-based resin in step S1 is one or more of soy protein resin, starch-based resin or polylactic acid resin.
4. The preparation method of the green and highly efficient enhanced wood-based panel according to claim 1, wherein, The nanocellulose in step S2 is cellulose nanocrystals or cellulose nanofibers prepared by mechanical treatment or enzymatic hydrolysis method.
5. The method for preparing the green and efficient reinforced wood-based panel according to claim 1, characterized in that: The mass ratio of the fluorosilane, aqueous acrylic emulsion and bio-based resin in step S1 is (1-5):(10-30):(5-20).
6. The preparation method of the green and highly efficient enhanced wood-based panel according to claim 1, wherein, The treatment time of the ultrasonic dispersion in step S1 is 10-20 minutes, and the frequency is 20-30 kHz.
7. The preparation method of the green and highly efficient enhanced wood-based panel according to claim 1, wherein, The weight ratio of the enhanced hydrophobic mixture to the raw wood-based panel materials in step S3 is (5-20):
100.
8. The method for preparing the green and efficient reinforced wood-based panel according to claim 1, characterized in that: The hot pressing temperature of the raw materials after sizing in step S4 is 160-190 °C, the pressure is 4-7 MPa, and the time is 5-12 minutes.
9. The preparation method of the green and highly efficient enhanced wood-based panel according to claim 1, characterized in that, The moisture content of the prepared green and highly efficient enhanced wood-based panel is controlled below 8%.
10. A green and highly efficient enhanced wood-based panel, characterized in that, It is prepared by the preparation method of the green and highly efficient enhanced wood-based panel according to any one of claims 1 to 9.
Citation Information
Patent Citations
Straw board for floor and manufacturing method and application of straw board
CN111483032A
Preparation method of multifunctional super-hydrophobic formaldehyde-free artificial board
CN112252069A
Shaving board and preparation method thereof
CN114714460A